Heterogeneous austenite grain growth in martensitic 9cr steel: coupled influence of initial metallurgical state and heating rate. (1st October 2013) - Zavaleta Gutiérrez, N.; Luppo, M. I.; Danon, C. A.; Toda-Caraballo, I.; Capdevila, C.; García de Andrés, C.
<x xml:space="preserve">Abstract</x> The coupled influence of the initial metallurgical state and the heating rate to austenite on the occurrence of heterogeneous grain growth during austenitisation of an ASTM A213-T91 steel has been studied. To that aim, two-step thermal cycles were designed. In the first step, different starting metallurgical conditions were obtained by treating the as received material at 780°C for increasing times up to 6 h. In the second step, in situ austenitisation was performed by heating to austenite at rates of 1, 30 and 50°C s−1 and then holding at 1050°C for 30'. Two types of austenite grain structures were obtained after austenitisation, namely, homogeneous and heterogeneous. The homogeneous structure was characterised by a smooth size distribution of approximately equiaxed, normally grown grains. The heterogeneous structure, instead, exhibited the exaggerated growth of a few austenite grains embedded in a small to medium sized matrix. For the 1°C s−1 heating rate and all of the initial metallurgical states, only homogeneous grain growth was observed, whereas for the 50°C s−1 heating rate only heterogeneous grain growth was observed regardless the starting metallurgical condition. Instead, the occurrence of homogeneous or heterogeneous grain growth after heating at 30°C s−1 was observed to be a function of the time of previous tempering. Some explanations of the phenomenon are advanced taking into account the precipitation state of second phases.